Palaeoenvironments around the Harappan Port of Lothal, Gujarat, western India - Khadkikar, A.S.; Basavaiah, N.; Gundurao, T.K .; Rajshekhar, C. (My University, 2004)
The palaeogeography and palaeoenvironments around Lothal, a Harappan port town, are reported based on remote sensing, environmental magnetic and Fourier transform infrared spectroscopy studies respectively. The results show that the uppermost part of the sediment record north of Lothal are characterized by low χ fd implying reduced monsoon rainfall. This reduction of monsoon rainfall was accompanied by high sea levels and is comparable with other global sea level and palaeoclimatic records.
Keywords: Palaeogeography; Monsoon rainfall; Western India; Environmental magnetic; Lothal